Development of potential Microbial Photosensitisers in the application of Photodynamic Therapy (Pdt) for the treatment of cancer and other diseases - Wong, Nyet Kui; How, Siew Eng; Lee, Hong Boon (Universiti Malaysia Sabah, 2010)
Photodynamic therapy (POn involves the administration of a nontoxic drug known as a photosensitiser, either systemically, locally, or topically to a patient bearing a lesion (frequently but not always cancer), followed by the illumination of the lesion with visible light (usually long wavelength red light), which, in the presence of oxygen, leads to the generation of cytotoxic species and consequently to cell death and tissue destruction. To date, few photosensitisers, such as Photofrin®, Levulan® and Foscan®, have been approved for PDT, but an ideal photosensitiser with regards to chemical purity, tumour selectivity, chemical and physically stability as well as rapid body elimination has not been found. Actinomycetes isolated from Sabah tropical forests soils, which could conceal potential therapeutic properties, were cultured aerobically for their secondary metabolites to screen for photocytotoxicity against human leukemic cell line HL60 using an MTT-based cell viability assay. 293actinomycetes strains were tested in the assay, but none of them showed to possess photocytotoxidty properties. Of these, 14 strains, namely Hlloo3, H11831, H11902, H7125, H7300, H7458, H7998, H8565, H8667, H8689, H8693, H8694, KA1016 and KAI022, showed marginal cytotoxic at a concentration of 100 ~gmL-l, and were further assayed at a concentration of 20 ~gmL-l. 3 crude extracts, namely Hll003, H7998 and H8565 showed cytotoxic activity and were subjected to purification for pure compound.